RESILIENCE OF SINGLE MOTHER MUSLIMAH WHO HAS CHILDREN WITH SPECIAL NEEDS (PSYCHOLOGY & MENTAL HEALTH) - Wafah, Sirril; Fahmawati, Zaki Nur (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This research aims to understand the resilience of Muslim single mothers who have children with special needs. The main focus of the research is how mothers deal with the psychological, emotional, and social challenges of parenting their children. Method: This research uses a qualitative approach with phenomenological methods. Data was collected through in-depth interviews with two informants who met the criteria as single mothers with children with special needs. Purposive sampling technique was used to select subjects who had demonstrated resilience in facing their life challenges. Results: Research finds that mothers' resilience is influenced by various aspects, including emotional regulation, impulse control, optimism, causal analysis, empathy, self-efficacy, and reaching out. Apart from that, social support, spirituality and positive emotions also play an important role in helping them overcome difficulties. Differences in resilience patterns were found between informants, with one relying more on social support, while the other focused more on self-control and confidence in facing challenges. Novelty: This research provides new insight into how resilience is formed in the context of single Muslim mothers with children with special needs. By understanding the aspects that support their psychological resilience, it is hoped that the results of this research can provide recommendations for other mothers who face similar situations and for those who want to provide support for families with children with special needs.